ANALISIS PENERAPAN KOMUNIKASI EFEKTIF DENGAN TEKNIK SBAR TERHADAP RESIKO INSIDEN KESELAMATAN PASIEN - Siska Novi Anggaraini; Leni Wijaya (Jurnal Kesehatan dan Pembangunan, 2026)
Effective communication is a crucial component of nursing care, particularly in ensuring patient safety. One communication method proven to be effective is the SBAR technique (Situation, Background, Assessment, Recommendation), which enables nurses to convey information in a structured, clear, and systematic manner, thereby reducing the potential for service errors. This study aimed to analyze the implementation of effective communication using the SBAR method in reducing the risk of patient safety incidents at Musi Medika Cendekia Hospital, Palembang. This study employed a quantitative design with a descriptive survey approach and a cross-sectional design. The sampling technique used was non-probability sampling with a total sampling method, involving 47 nurses who met the inclusion and exclusion criteria. Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test. The results showed that the majority of respondents had a low risk of patient safety incidents, with 30 respondents (63.8%). The implementation of effective SBAR communication was also predominantly categorized as good, with 30 respondents (63.8%). Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant relationship between the implementation of effective SBAR communication and the risk of patient safety incidents. In conclusion, better implementation of SBAR communication by nurses is associated with a lower risk of patient safety incidents. Therefore, continuous improvement of communication skills, particularly the SBAR technique, is strongly recommended to enhance the quality of nursing care and prevent adverse events.